Health conditions, physical disabilities, perceived burdensomeness, and depressive symptoms influence suicidal ideation. Issue 4 (21st April 2017) - Khazem, Lauren R.; Jahn, Danielle R.; Cukrowicz, Kelly C.; Anestis, Michael D.
ABSTRACT: The roles of perceived burdensomeness and depressive symptoms in the relationship between physical disabilities or health conditions and suicidal ideation warrant examination. The authors examined indirect effects using cross-sectional data from adults who answered questions online. The serial indirect effect of the number of physical disabilities on suicidal ideation through perceived burdensomeness and depressive symptoms was not significant, but the serial indirect effects of the combined number of physical disabilities and health conditions and number of health conditions on suicidal ideation through perceived burdensomeness and depression were each significant. For those with disabilities or health conditions, perceived burdensomeness may precede depressive symptoms in the development of suicidal ideation.